Diary of Samuel Pepys $1 (BVolume 73: April/May 1669s - Pepys, Samuel, 1633-1703; Braybrooke, Richard Griffin, Baron, 1783-1858; Wheatley, Henry B. (Henry Benjamin), 1838-1917; Bright, Mynors, 1818-1883 (Salt Lake City, UT : Project Gutenberg, 2003)
"Diary of Samuel Pepys $1 (BVolume 73: April/May 1669" by Samuel Pepys is a historical diary written in the late 17th century. This volume captures a specific period in Pepys' life, detailing his experiences and observations as a Clerk of the Acts and Secretary to the Admiralty in England. The diary offers insights into various facets of life during the Restoration period, including naval affairs, social interactions, domestic life, and reflections on personal health. The opening of this volume starts with excerpts from early April 1669, chronicling Pepys' activities as he navigates court-martial proceedings, social dinners, and his responsibilities at the Navy Office. Pepys exhibits a keen awareness of political dynamics, taking note of discussions around Navy administration and the influence of various figures, such as the Duke of York. His personal life intertwines with these observations, revealing a mix of social gatherings and introspective thoughts on relationships and his own eye problems. This portion of the diary emphasizes Pepys' dual role in public service and private life, setting the stage for a deeper understanding of his character and the historical context in which he lived. (This is an automatically generated summary.)s
Release date is 2003-06-01
Produced by David Widger
Keywords: Pepys, Samuel, 1633-1703 -- Diaries; Cabinet officers -- Great Britain -- Diaries; Diarists -- Great Britain -- Diaries; Great Britain -- Social life and customs -- 17th century -- Sources; Great Britain -- History -- Charles II, 1660-1685 -- Sources